Peer firms in relative performance evaluation - Albuquerque, Ana (Journal of Accounting and Economics, 2009)
Relative performance evaluation (RPE) in chief executive officer (CEO) compensation provides insurance against external shocks and yields a more informative measure of CEO actions. I argue that empirical evidence on the use of RPE is mixed because previous studies rely on a misspecified peer group. External shocks and flexibility in responding to the shocks are functions of, for example, the firm's technology, the complexity of the organization, and the ability to access external credit, which depend on firm size. When peers are composed of similar industry-size firms, evidence is consistent with the use of RPE in CEO compensation.